The fast-track surgery program application after pancreaticoduodenectomy, using interintestinal anastomosis in accordance to Brown procedure - O. Yu. Usenko; A. A. Skums (Клінічна хірургія)
Objective. To estimate the impact of formation of gastroenteroanastomosis with Brown’s anastomosis, while performing of pancreatico-duodenectomy, on the gastric evacuation arrest rate in a frame of the fast-track surgery program implementation.